Pengaruh Komitmen Dan Kompensasi Terhadap Kinerja Karyawan Pada PT. Dipa Pharmalab Intersains Di Jakarta - Dion Arifianto; Aryanda Aryanda (Manajerial, 2015)
The objectives in this research are describe influence of commitment and compensation in partially and simultaneous on the performance of employees of PT. Dipa Pharmalab Intersains in Jakarta. This research uses a quantitative descriptive analysis. The populations in this research are the employee of PT. Dipa Pharmalab Intersains in Jakarta, while the sample using simple random sampling technique, which determines the sample, in order to obtain the total sample of 109 people. The results showed that the employee performance was predicted by commitment and compensation . In other words, commitment and compensation has been a role in increasing employee performance in the PT. Dipa Pharmalab Intersains in Jakarta. The results are proved that employee performance was simultaneous affected by commitment and compensation.